HLA‐C*15:29, an HLA‐C*15 variant, identified in a Taiwanese individual. (24th May 2018) - Yang, K. L.; Lin, P. Y.
Abstract : One nucleotide substitution at codon 116 of HLA‐C*15:02:01:01 results in a new allele, HLA‐C*15:29 .